Targeted ultrasound and fine-needle aspiration cytology for sentinel node diagnostics in early-stage melanoma: a validation study. Issue 4 (August 2018) - Ternov, Niels K.; Lambine, Trine-Lise; Wagenblast, Anne L.H.; Clasen-Linde, Erik; Oturai, Peter S.; Klyver, Helle; Nielsen, Kristina R.; Nielsen, Michael B.; Drzewiecki, Krzysztof T.; Chakera, Annette H.
Abstract : Ultrasound-guided fine-needle aspiration cytology (US-FNAC) is used to evaluate the involvement of lymph nodes in various malignant diseases. Its value in detecting sentinel lymph node (SN) metastasis preoperatively in melanoma patients is controversial and is the subject of this study. In this prospective validation study, 91 consecutive patients with melanoma clinical stage I ( n =64) and II ( n =27) were examined with US-FNAC before SN biopsy from 2012 to 2014 at a tertiary center. All patients underwent lymphoscintigraphy before the US-FNAC. Lymph nodes that showed any of the Berlin morphologic criteria on ultrasonography were examined using FNAC. The median Breslow thickness of the melanomas was 1.22 mm (range: 0.47–11.5 mm). Twenty-two percent of the patients had metastases in their SNs, 90% of which were smaller than 2 mm in largest diameter. The percentages of metastases with a size more than 1 mm were 50 and 29%, respectively, in the true-positive and false-negative US groups. The sensitivity, specificity, positive predictive value, and negative predictive value for overall US examination were 30, 81, 24, and 83%, respectively. None of the FNACs contained conclusive malignant cells. The specificity of the FNAC was 76%. Our results show that US-FNAC was not a useful diagnostic tool in our setting as it did not add significantly to the staging and management of patients with mainly thin cutaneous melanomas, perhaps because of the often small size of the SN metastases. It may be useful in the early diagnosis of lymph node metastases in a subgroup of melanoma patients with larger metastases.